Qualitative (phytochemical) analysis and antifungal activity of Pentas decora (De wild), a plant used traditionally to treat skin fungal infections in Western Uganda - Ahumuza, Taddeo; Claude, Kirimuhuzya (Research in Pharmaceutical Biotechnology, 2011)
The ethanolic leaf extract of Pentas decora, a plant known in the local community as “Kabyakyasha” (in Runyankole Language), was evaluated for its antifungal activity against Candida albicans, Epidermophyton floccosum, Microsporum canis and Trichophyton rubrum, and qualitatively analyzed for its phytochemical composition. The disc diffusion method was employed to determine the antifungal activity. Minimum inhibitory concentrations (MICs) and minimum fungicidal concentrations (MFCs) were also determined using the tube dilution method. The Pentas decora ethanolic extract exhibited activity against C. albicans and M. canis, with MICs of 1000 and 1500 mg/ml respectively, while the corresponding values for the standard drug (clotrimazole) were 50 and 100 mg/ml respectively. The MFC values of the extract for C. albicans and M. canis were 2000 and 2500 mg/ml respectively while the corresponding MFC values for clotrimazole were 100 and 150 mg/ml respectively. However, both the extract and the standard drug had no activity against E. fluccosum and T. rubrum. The extract was also found to be rich in alkaloid and terpenoids. It can be concluded that the plant has some antifungal activity but there is need to do more tests and first ascertain its toxicity profile before it is declared sufficiently efficacious and safe for use by the community.
Keywords: Pentas decora; Anti fungal activity; Skin fungal infections